Voces indígenas en letras españolas: algunos aspectos morfosintácticos del contacto colonial - Mendoza Posadas, Mauro Alberto (2016)
In this article an approach is made to the morphosyntactic features of 9 documents that come from different archives of central Mexico; these documents show a clear interference between the Nahuatl and the Spanish languages of the XVII and XVIII centuries, and all of them were wrote by nahuatl speakers. The interferences presented in the documentation is the reduplication of the Direct Object, the absence of the preposition ‘a’ as case marker, the absence of the agreement between a noun and its adjective, and the generalized use of the preposition ‘en’ as locative marker.